2020
DOI: 10.18488/journal.61.2020.83.379.393
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Maritime Learning Activities on the Development of Student Competencies: Case Study

Abstract: This study aimed to test the impact of government commitment, curriculum development, and education and training, either directly or indirectly through school management and business actors' participation in maritime learning activities to develop student competencies. This research was conducted in five junior high schools in North Jakarta and Java provinces, Indonesia. The sample size was 175 students of grade IX selected through random sampling techniques. Data was collected through a questionnaire distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In essence, the success of entrepreneurship education depends on the presence of capable educators, who demonstrate the importance of their competence in fostering learning citizens dedication to learning related to entrepreneurship. Furthermore, (Hidayati et al, 2020) in the context of maritime entrepreneurship learning, showed that students see support from the role of business actors in the field of skills in maritime more directed at the importance of internships/practical training in companies with expert teaching staff and complete facilities needed. As for the context of instructor competence, business actors who are outside the teaching experts are assumed to be relevant to the entrepreneurial competencies possessed by the instructors, in this case entrepreneurship educators or instructors are taken from business actors.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the success of entrepreneurship education depends on the presence of capable educators, who demonstrate the importance of their competence in fostering learning citizens dedication to learning related to entrepreneurship. Furthermore, (Hidayati et al, 2020) in the context of maritime entrepreneurship learning, showed that students see support from the role of business actors in the field of skills in maritime more directed at the importance of internships/practical training in companies with expert teaching staff and complete facilities needed. As for the context of instructor competence, business actors who are outside the teaching experts are assumed to be relevant to the entrepreneurial competencies possessed by the instructors, in this case entrepreneurship educators or instructors are taken from business actors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MSGI from Singapore provides a blueprint for addressing environmental concerns, aligning with global sustainability goals. Integrating such initiatives into the Indonesian maritime education policy could create environmentally conscious maritime leaders [16].…”
Section: Relevance To the Indonesian Contextmentioning
confidence: 99%
“…Marine teaching materials are a need for students to introduce maritime culture [36]. Maritime learning positively influences students [37], [38]. In teaching maritime education, the characteristics of a competent teacher are needed [39], [40].…”
Section: Improving Student's Character Value Through Using Character-...mentioning
confidence: 99%